An interesting case of anal melanoma caused liver metastases due to misdiagnosed as hemorrhoids - Akar, Tarık (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Akar T. An interesting case of anal melanoma caused liver metastases due to misdiagnosed as hemorrhoids.Turk J Gastroenterol 2018; 29: 619-20.